Kinin B2 and B1 Receptors Activation Sensitize the TRPA1 Channel Contributing to Anastrozole-Induced Pain Symptoms - Maria Fernanda Pessano Fialho; Evelyne Silva Brum; Gabriela Becker; Indiara Brusco; Sara Marchesan Oliveira (MDPI AG, 2023)
Aromatase inhibitors (AIs) cause symptoms of musculoskeletal pain, and some mechanisms have been proposed to explain them. However, signaling pathways downstream from kinin B2 (B2R) and B1 (B1R) receptor activation and their possible sensitizing of the Transient Receptor Potential Ankyrin 1 (TRPA1) remain unknown. The interaction between the kinin receptor and the TRPA1 channel in male C57BL/6 mice treated with anastrozole (an AI) was evaluated. PLC/PKC and PKA inhibitors were used to evaluate the signaling pathways downstream from B2R and B1R activation and their effect on TRPA1 sensitization. Anastrozole caused mechanical allodynia and muscle strength loss in mice. B2R (Bradykinin), B1R (DABk), or TRPA1 (AITC) agonists induced overt nociceptive behavior and enhanced and prolonged the painful parameters in anastrozole-treated mice. All painful symptoms were reduced by B2R (Icatibant), B1R (DALBk), or TRPA1 (A967079) antagonists. We observed the interaction between B2R, B1R, and the TRPA1 channel in anastrozole-induced musculoskeletal pain, which was dependent on the activation of the PLC/PKC and PKA signaling pathways. TRPA1 seems to be sensitized by mechanisms dependent on the activation of PLC/PKC, and PKA due to kinin receptors stimulation in anastrozole-treated animals. Thus, regulating this signaling pathway could contribute to alleviating AIs-related pain symptoms, patients' adherence to therapy, and disease control.